Creating safe(r) spaces for difficult conversations in law classrooms: guidelines for university lecturers - Geduld, Allison Jade Nicole (Frontiers in Education, 2025)
Difficult conversations often take place in university classrooms. While intellectual debate has always been part of higher education's remit, the complexity around uncomfortable and difficult conversations has been compounded by cancel culture and virtue signaling —phenomena that are both closely associated with the information age. Difficult classroom conversations are an unavoidable part of the development of critical thinking. However, the present-day phenomenon of safe spaces often works against this ideal in that students can feel unsafe when confronted with uncomfortable topics and choose to avoid them. The question therefore arises: How can safe spaces be created within classrooms to best develop the required critical thinking skills and graduate attributes? This article delves into the notion of safe spaces at universities and offers some strategies for safe(r) spaces where lecturers are intentional about their classroom practices before, during and after lectures.